Frailty identification and management among Brazilian healthcare professionals: a survey - Azevedo, Paula Schmidt [UNESP]; de Melo, Ruth Caldeira; Souza, Juli Thomaz de [UNESP]; Frost, Rachael; Gavin, James P.; Robinson, Katie; Boas, Paulo José Fortes Villas [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Aprahamian, Ivan; Wachholz, Patrick Alexander [UNESP]; Hinslif-Smith, Kathryn; Gordon, Adam Lee (Springer Nature, 2024)
Background: National and international guidelines on frailty assessment and management recommend frailty screening in older people. This study aimed to determine how Brazilian healthcare professionals (HCPs) identify and manage frailty in practice. Methods: An anonymous online survey on the assessment and management of frailty was circulated virtually through HCPs across Brazil. Results: Most of the respondants used non-specific criteria such as gait speed (45%), handgrip strength (37.6%), and comprehensive geriatric assessment (33.2%). The use of frailty-specific criteria was lower than 50%. The most frequently used criteria were the Frailty Index (19.1%), Frailty Phenotype (13.2%), and FRAIL (12.5%). Only 43.5% felt confident, and 40% had a plan to manage frailty. In the multivariate-adjusted models, training was the most crucial factor associated with assessing frailty, confidence, and having a management plan (p < 0.001 for all). Those with fewer years of experience were more likely to evaluate frailty (p = 0.009). Being a doctor increased the chance of using a specific tool; the opposite was true for dietitians (p = 0.03). Those who assisted more older people had a higher likelihood of having a plan (p = 0.011). Conclusion: Frailty assessment was heterogeneous among healthcare professions groups, predominantly using non-specific criteria. Training contributed to frailty assessment, use of specific criteria, confidence, and having a management plan. This data informs the need for standardized screening criteria and management plans for frailty, in association with increasing training at the national level for all the HCPs who assist older people.
Keywords: Brazil; Frailty; Frailty criteria; Healthcare professionals; Older people; Survey